Easy to use accurate measuring system for cycling pedaling motion using a small LED and a smartphone - Fukuda, M. (Journal of Science and Cycling, 2019)
We already know heel motion affect torque pattern. But we don't measure heel motion easily so far. And we need to measure motion with high accurate. And more these motion is difficult to know from just number. So we developed high accurate motion measurement system with LED. We can easy to understand that rider's pedaling are different.